THE INFLUENCE OF THIAMINE IN THE FERMENTATION OF THE WINE YEASTS - Ovidiu Tita; Letitia Oprean; Mihaela Tita; Eniko Gaspar; Nicoleta Mandrean; Mariana Pacala; Ecaterina Lengyel (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Due to the enzymatic equipment, the yeast cell produces alcoholic fermentation by the meaning of a zimazic complex which catalyzes in different stages the redox processes of the carbohydrates, which are able to ferment, ultimately leading to ethanol. The fermentation rate is an exponential function being influenced by the cells concentration in the development environment and the starter cultures of micro-organisms. Most of the yeast strains do ferment some substrates rich in hexosanes and oligoglucides: sucrose, maltose, raffinose, lactose and celobiose. The biomass quantity may be increased in various ways. An important aspect in the increasing of the multiplication rate of the yeast cells is the determination of the optimum growing conditions. Some kinetic dependencies, mono and multi-factorial, have been observed; they describe the impact of the concentration of the base components in the nutrient environment, temperature, pH, mixing intensity on the multiplication rate of the yeasts.